2019
DOI: 10.1111/fare.12389
|View full text |Cite
|
Sign up to set email alerts
|

Parental Confirmation, Body Dissatisfaction, and Disordered Eating Behaviors Among Female College Students

Abstract: Objective To examine whether parental communication is associated with body dissatisfaction and disordered eating among college‐age daughters and whether these associations are mediated by psychological well‐being. Background Appearance‐related parental comments such as weight criticism have been shown to contribute to daughters' body dissatisfaction and disordered eating. Yet less is known about how the general quality of parental communication that is not directly related to appearance is associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…In this study, the role of the father seems to be less relevant in predicting coping with difficulties , with father’s control and protection appearing with a significant negative impact in developing coping abilities. These results on the influences of mother’s and father’s rearing patterns reflect (at the university level) the main studies done at different educational levels (Batool, 2019 ; Bully et al, 2019 ; Franco et al, 2014 ; Fuentes et al, 2015 ; Gómez et al, 2015 ; Gordon & Cui, 2012 ; Kim et al, 2020 ; Masud et al, 2019 ; Moral et al, 2020 ; Njega et al, 2019 ; Robledo & García, 2009 ; Taniguchi, 2019 ).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In this study, the role of the father seems to be less relevant in predicting coping with difficulties , with father’s control and protection appearing with a significant negative impact in developing coping abilities. These results on the influences of mother’s and father’s rearing patterns reflect (at the university level) the main studies done at different educational levels (Batool, 2019 ; Bully et al, 2019 ; Franco et al, 2014 ; Fuentes et al, 2015 ; Gómez et al, 2015 ; Gordon & Cui, 2012 ; Kim et al, 2020 ; Masud et al, 2019 ; Moral et al, 2020 ; Njega et al, 2019 ; Robledo & García, 2009 ; Taniguchi, 2019 ).…”
Section: Discussionmentioning
confidence: 71%
“…This concept of DinL was operationalized as a construct based on the literature on the field and on a preliminary study (see below), comprising five psychological dimensions: (1) Coping with difficulties includes the degree to which the student abates or regulates mental health difficulties related to learning, such as anxiety, irritability, discouragement, apathy, poor performance expectations, difficulties in the place of study, distortions on achievement attributions, low self-esteem, low perceived self-efficacy, and negative attitudes of the class group (Aliberti et al, 2019 ; Álvarez & Fernández, 2005 ; Batool, 2019 ; Chiodelli et al, 2018 ; Del Valle et al, 2020 ; Heritage et al, 2023 ; Khalil et al, 2020 ; Lew et al, 2019 ; MacCann et al, 2020 ; Matalinares et al, 2016 ; Morales & Pérez., 2019 ; Njega et al, 2019 ; Robledo & García, 2009 ; Taniguchi, 2019 ; Tinajero et al, 2020 ; Trunce et al, 2020 ; Weinstein et al, 2002 ). The studies on cognitive, emotional, or psychosocial difficulties and family/social stressors affecting learning show that these difficulties feed each other if not treated early using inclusive and integrative approaches (e.g., Asante & Andoh-Arthur, 2015 ; Chiodelli et al, 2018 ; Ibrahim et al, 2013 ; January et al, 2018 ; Lamis et al, 2016 ; Lew et al, 2019 ; Mirza et al, 2021 ; Samaniego & Buenahora, 2016 ; Santander et al, 2013 ; Tian-Ci Quek et al, 2019 ; Trunce et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there tends to be more focus and discussion on mother-daughter interactions in the body image literature (Cooley et al, 2008), we argue that each interpersonal source (i.e., fathers, sisters) is important and will contribute to Latinas’ mental health (Chow & Tan, 2018; Romo & Mireles-Rios, 2016). In fact, researchers have found that close relationships with fathers promotes healthy eating and well-being in female colleges students (Taniguchi, 2019). Extending the current literature to examine messages from sisters is critical because sisters’ messages may also be salient, especially in this cultural group.…”
Section: Introductionmentioning
confidence: 99%